PERANAN PEREMPUAN PENJUAL POSTCARD DI KAWASAN DAYA TARIK WISATA KHUSUS TANAH LOT DALAM SEKTOR DOMESTIK DAN PUBLIK - Kumala Pratiwi, Luh Putu Aritiana; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 1 No 1 (2013): VOL 1, NO 1 (2013): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2013)
ABSTRACT Effect on the development of tourism and economy wide employment opportunities for the people including women. Understanding in society that women are only responsible for the domestic sector, and the public sector only the responsibility of men. This is not always true because there are also women working public sector, workers are women postcard sellers. Therefore the inclusion of women into the public world, requires women to be able to complete the task of domestic primary responsibility.To uncover problems in the research using primary and secondary data sources, while the type of data used is also quantitative and qualitative data. Methods of collecting data through observation, interviews, and library research. Analysis of the data used is descriptive qualitative analysis. The results showed that the role of women in the domestic sector postcard sellers are set up housekeeping (cleaning the house, washing clothes, cooking, cleaning the home furnishings), child care, and social activities in the community such as cremation, temple ceremony, marriage. The role of the public sector women are selling postcard.
Keywords: Keywords : Women, Responsibility, Postcard sellers